The impact of Environmental Accounting Information System Alignment on Firm Performance and Environmental Performance: A case of Small and Medium Enterprises s of Indonesia - Susanto, Azhar; Meiryani, Meiryani (International Journal of Energy Economics and Policy, 2019)
The current research investigates the empirical debate that impact of alignment environmental accounting information system on firm performance and environmental performance. For doing this purpose, the current study examines the impact of environmental requirement and environmental capability on alignment of accounting information system. Furthermore, the study investigates the effect of environmental alignment on firm performance and environmental performance. The current study is conducted in the small-medium enterprises in Indonesia. The results of structural equation modeling confirm that EAIS requirement and EAIS capability have a positive and significant impact on EAIS alignment. Moreover, the results also confirm that EAIS alignment has a positive and significant impact on firm performance and environmental performance in Indonesia. Alongside, the study also implies that the responsiveness of the organization towards environmental needs is critical not only to the nature but to the organization itself in building corporate image, sustainable practices and certifications that enhance organization repute and managers understanding of the environmental need along with improved societal commitments. Keywords: Environmental accounting information system, firm performance, environmental performance, Indonesia. JEL Classifications: E01, L25, Q01 DOI: https://doi.org/10.32479/ijeep.7511